Rancang Bangun Sistem Monitoring Suhu dan Kelembapan Berbasis IoT Pada Filter G4 Ventilasi PV Box - Rafly Hadi Pangestu; Paniran Paniran (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
As time goes by, the rapid development of technology has brought various conveniences to people's daily activities. An example of the continuation of technology is microcontrollers and electronic devices that can be connected to the network. One of them is the industrial sector in the PLTS plant at the 7 Mwp On-Grid PLTS Pt. Infrastructure Terbarukan Cemerlang Sengkol which has PV Box generating equipment that requires temperature and humidity control to determine the cause of corrosion that occurs in the PV Box.This study is intended as a solution in monitoring PV Box generating equipment. This technology development uses the Internet of Things (IoT) which combines the physical and virtual worlds. In this research, the method used is the experimental measurement method, making the system created more real and detailed. In research using DHT11 equipment which has the advantage of being able to estimate temperature and humidity. NodeMCU ESP32 as a microcontroller connected to the blynk platform via the internet functions to manage hardware, show evidence of sensors, secure data, depict data, and others. The results of the research on designing a temperature and humidity monitoring system at the 7 Mwp On-Grid PLTS Pt. Infrastructure Terbarukan Cemerlang Sengkol were successfully created and produced positive effects by being monitored using the blynk platform. This research was carried out in real time using a cell phone wherever you are. This research shows that temperature measurements from the DHT11 sensor obtained an average temperature of 31.78%, while the average humidity value was 85.96%, which indicates that the room being measured had high humidity. By considering these two findings, it can be concluded that the cause of corrosion in the room is high humidity and redox reactions from various substances in the environment.